(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper aims at analyzing the utopian aspect of American society in F.S. Fitzgerald’s (1896-1940) The Great Gatsby (1925). “The Great Gatsby “ is known as a the work where all ideal society features are described, where utopian definitions are given. It aims at depicting those aspects of the society through a careful examination of the settings, particularly East egg and the Valley of Ashes. Utopian views in the work represent the protagonist’s ideal reality in which he dreams of becoming famous, wealthy, and more satisfied.